Significance of an amorphous SiO2 phase in a pseudomorph after coesite enclosed in garnet from ultrahigh‐pressure eclogite, Su–Lu Belt, eastern China. (20th April 2018) - Taguchi, Tomoki; Miyake, Akira; Enami, Masaki; Igami, Yohei
Abstract: Here, we report the first discovery of an amorphous SiO2 phase (APSI phase) in a pseudomorph after coesite included in garnet from an ultrahigh‐pressure (UHP) eclogite from the Su–Lu metamorphic belt, eastern China. Using transmission electron microscopy, Raman spectroscopy and selected area electron diffraction, we show that the internal structure of the pseudomorph consists of an APSI phase with nano/submicrocrystalline particles of quartz and a polycrystalline K‐bearing fibrous sheet‐silicate phase (KFSS phase). The APSI phase‐bearing aggregates included in the garnet might have formed by reactions involving a supercritical fluid during exhumation by the following processes: (1) the development of radial cracks within the host garnet by the phase transition of coesite to quartz; (2) the decomposition of a part of the pseudomorph following infiltration of supercritical fluid; (3) the precipitation of the KFSS phase from the fluid phase during subsequent exhumation and cooling, which was likely promoted by a change in the metamorphic fluid from supercritical and/or subcritical to aqueous fluid; and (4) the rapid precipitation of the APSI phase under a metastable (non‐equilibrium) state, such as quenching, during a later stage of the exhumation. Whether the APSI phase generally formed during exhumation and survived widely throughout the Su‐Lu terrane is unknown. However, the presence of the APSI phase in a UHP eclogite provides new insight into the geodynamic phenomena occurring at continental collision zones.